2017
DOI: 10.18276/cej.2017.1-01
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Warm-up Duration on Cycling Time Trial Performance in Trained Cyclists

Abstract: The purpose of this study was to assess the effects of three different warm-up condi-tions on a 5K cycling time trial (TT).Sixteen trained cyclists completed the study. At the first testing session, participants completed a maximal graded exercise test to assess maximal oxygen consumption (VO 2 max) and a familiarization of the TT. At three subse-quent visits, the participants completed the TT after no warm up, short warm-up of three minutes at 60% VO 2 max, or long warm-up of ten minutes at 60% VO 2 max. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(56 reference statements)
1
1
0
Order By: Relevance
“…8 In this study, it was found that a short, specific WU elicited similar physiological responses, perception of effort and subsequent sprint time-trial performance compared to a longer, more traditional approach. This is, in part, consistent with previous research acknowledging the potential for longerduration WUs to result in fatigue, 6,[8][9][10][11] while shorter WUs have been reported to enhance physiological and/or performance measures in rowing 6 and track cycling. 11 While the aforementioned study investigated WU approaches in sprint XC skiing, no research has been conducted to date on WU strategies prior to distance XC skiing.…”
Section: Introductionsupporting
confidence: 90%
“…8 In this study, it was found that a short, specific WU elicited similar physiological responses, perception of effort and subsequent sprint time-trial performance compared to a longer, more traditional approach. This is, in part, consistent with previous research acknowledging the potential for longerduration WUs to result in fatigue, 6,[8][9][10][11] while shorter WUs have been reported to enhance physiological and/or performance measures in rowing 6 and track cycling. 11 While the aforementioned study investigated WU approaches in sprint XC skiing, no research has been conducted to date on WU strategies prior to distance XC skiing.…”
Section: Introductionsupporting
confidence: 90%
“…These studies proposed that a metabolic acidosis is necessary for the VO 2 response profile to be altered in the second exercise bout. But Koppo, Bouckaert [8] showed a prior sub maximal exercise similar the prior heavy exercise VO 2 response was reduced during the second bout of exercise [9]. The purpose of this study was to examine the effects of prior (warm-up) exercise on pulmonary oxygen uptake at the end of sub maximal exercise in elite female futsal players.…”
Section: Introductionmentioning
confidence: 93%